Answer:
126?
Step-by-step explanation:
Can you translate i can help you better
Answer:
![\frac{-27}{2} = (-13)(\frac{1}{2})](https://tex.z-dn.net/?f=%5Cfrac%7B-27%7D%7B2%7D%20%3D%20%28-13%29%28%5Cfrac%7B1%7D%7B2%7D%29)
Step-by-step explanation:
The given equation is 4 + 2/3 x = -5
Taking variable on one side and constants on other side, we get
![-9 = (\frac{2}{3})(x)](https://tex.z-dn.net/?f=-9%20%3D%20%28%5Cfrac%7B2%7D%7B3%7D%29%28x%29)
![x = (\frac{3}{2})(-9) = \frac{-27}{2} = (-13)(\frac{1}{2}) = -13.5](https://tex.z-dn.net/?f=x%20%3D%20%28%5Cfrac%7B3%7D%7B2%7D%29%28-9%29%20%3D%20%5Cfrac%7B-27%7D%7B2%7D%20%3C%2Fstrong%3E%3C%2Fp%3E%3Cp%3E%3Cstrong%3E%3D%20%28-13%29%28%5Cfrac%7B1%7D%7B2%7D%29%20%3D%20-13.5)
The number in decimal form is given by -13.5
The number in fraction form is given as ![\frac{-27}{2} = (-13)(\frac{1}{2})](https://tex.z-dn.net/?f=%5Cfrac%7B-27%7D%7B2%7D%20%3D%20%28-13%29%28%5Cfrac%7B1%7D%7B2%7D%29)
4.5/3 = x/5
then:
x = 5 * 4.5 / 3 = 15/2 = 7.5
hope that helps